PENGEMBANGAN PANGAN FUNGSIONAL BERBASIS PANGAN LOKAL SEBAGAI PRODUK SARAPAN UNTUK REMAJA GEMUK - Darawati, Made; Riyadi, Hadi; Damayanthi, Evy; Kustiyah, Lilik (Jurnal Gizi dan Pangan, 2016)
This study aimed to find a functional food formulas (FFF) based on local food as breakfast product, that can be accepted organoleptically, nutritious, and contain antioxidants for overweight/obese adolescents. This study was laboratory experiment, randomized complete design and using five level of one factor of treatment (proportion of carrot: pumpkin were F1 7.14%:19.64%; F2 8.93%:17.86%; F3 10.71%:16.07%; F4 12.50%:14.29%; and F5 14.29%:12.50%). The result showed that 80-100% of semi-trained panelis accepted all FFFs (F1, F2, F3, F4, and F5) organoleptically. There was a significant effect of level of treatment (F1, F2, F3, F4, and F5) on the color, flavor, and overall of FFFs (p<0.05). Product F5 had the highest percentage of acceptance and the average value than other products. F5 consisted of 30.36% orange sweet potato, 28.57% red beans, 8.93% fermented soybean (tempeh), 14.29% carrot, 12.50% pumpkin, 3.75% sugar, and 1.79% cornstarch. Each portion of F5 product could contribute about 20% of the recommended energy and protein adequacy for adolescents, and it’s contain 4.02 mg of β-carotene and antioxidant activity 38.54 mg/100 g (AEAC). The total microbe content of F5 was 9.6 x 102 coloni/g, still below the threshold for a type of processed product, so that these products are safe to eat. The resulting product has the potential as a functional food because of the content of β-carotene and it's antioxidant activity and can be considered as a breakfast product for overweight/obese adolescents.Keywords: adolescent, functional food, local food, obese, overweight